Current clinical practice guidelines on chemotherapy and radiotherapy for the treatment of non-metastatic muscle-invasive urothelial cancer: A systematic review and critical evaluation by the Hellenic Genito-Urinary Cancer Group (HGUCG). Issue 1 (January 2015) - Zagouri, F.; Peroukidis, S.; Tzannis, K.; Kouloulias, V.; Bamias, A.; on behalf of the Hellenic Genito-Urinary Cancer Group (HCUCG)
Abstract Radical cystectomy is the treatment of choice in localized muscle-invasive urothelial cancer. Nevertheless, relapses are frequent and systemic chemotherapy has been employed in order to reduce this risk. In addition, bladder preservation strategies are appealing. During the last decade, there has been a difficulty in conducting and completing large-scale trials in urothelial cancer. This has resulted in relatively few changes in the existing guidelines. Recent studies have created renewed interest in certain fields, such as the role of chemo-radiotherapy and management of unfit patients. In addition, application of certain guidelines has been limited in everyday practice. We conducted a systematic review of the existing guidelines and recent randomized trials not included in these guidelines, and developed a treatment algorithm, regarding non-surgical therapies for non-metastatic, muscle-invasive urothelial cancer based predominantly on patients' fitness for the available therapeutic modalities.